Dr. Pavel Turner in Študijska knjižnica v Mariboru - Hartman, Bruno (Studia Historica Slovenica, 2001)
In the paper, the role of Dr. Pavel Turner, as the president of the Maribor Historical society, at the beginning of the XX century, as to the establishment of the library society, is depicted. He substantially supported it and by his testament he left it an opulent estate of books
Keywords: biografije; izobraženci; kulturna zgodovina; Maribor; slovenska inteligenca; Turner, Pavel; znameniti Slovenci